Math, asked by abdulhafidh345, 6 months ago

f A = B = 45°, show that:
(i) sin (A - B) = sin A cos B - cos A sin B
(ii) cos (A + B) = cos A cos B - sin A sin B

Answers

Answered by asdeepsingh777
2

Step-by-step explanation:

(i) L.H.S= sin (A - B) = sin ( 45 - 45) = 0

R.H.S = Sin 45° cos 45° - cos 45° sin 45°

=

 \frac{1}{ \sqrt{2} }  \times  \frac{1}{ \sqrt{2} }  -  \frac{1}{ \sqrt{2} }  \times  \frac{1}{ \sqrt{2} }

= 0 = L.H.S, Proved

(ii) L.H.S= cos (A + B) = Cos( 45 + 45) =cos(90°)

= 0

R.H.S = cos 45° cos 45° - sin45° sin 45°

=

 \frac{1}{ \sqrt{2} } \times  \frac{1}{ \sqrt{2} }  -  \frac{1}{ \sqrt{2} } \times  \frac{1}{ \sqrt{2} }

= 0 = L.H.S ,

proved.

Similar questions